Strong and weak lensing by galaxy clusters - Bartelmann, Matthias (Arxiv, 2002)
I present an overview of strong and weak gravitational lensing by galaxy clusters. After briefly introducing the principles of gravitational lensing, I discuss the main lessons learned from lensing on the mass distribution in clusters and their relation to cosmology.
Gesehen am 26.09.2017